The effect of earth pressure on the failure mode of high-speed railway tunnel linings. (March 2020) - He, Ben-Guo; Li, Hong-Pu; Zhang, Zhi-Qiang
Graphical abstract: Highlights: The failure mode of a tunnel lining depends on the earth pressure coefficient, K . The mechanical behavior of the tunnel lining is most favorable when 0.6 <  K  < 1.2. Designers need to take K into account when a lining is designed. The value of K suggests which parts of the lining are most likely to fail. Abstract: The effect of earth pressure on the mechanical behaviour of horseshoe-shaped tunnel linings was explored using 1:30 scaled models. The linings considered are typically used to carry 300 km/h high-speed trains on double tracks. A self-weight stress field causes the tunnel lining's roof settlement to dominate over the horizontal deformation of the walls. In contrast, a horizontal tectonic stress field causes the knees of the lining to bend outwards and the walls to bend inwards. These differences must be taken into account when formulating the design parameters for the lining. The cracking pattern observed in the tunnel lining coincides with the bending distribution, but does not reflect the deformation very well when subjected to its own self-weight stress field. The most favourable mechanical behaviour of the tunnel lining occurs when the coefficient of lateral pressure K has values ranging from 0.6 to 1.2. When K is less than 0.6, flexural failure occurs at the intrados of the lining's roof and the extradoses of the shoulders. However, when K is greater than 1.2, the knees of the lining become the most vulnerable locations. A series of destructive tests were also performed which yielded a high correlation between the cracking pattern and the coefficient of lateral pressure. The experimental results were further supported by performing nonlinear finite-element numerical modeling.